HUBUNGAN ANTARA KESIAPAN BELAJAR DENGAN KOMPETENSI INTI PENGETAHUAN BAHASA INDONESIA PADA SISWA KELAS V SD GUGUS LETKOL WISNU DENPASAR UTARA TAHUN PELAJARAN 2017/2018 - Ni Putu Trisna Hendrayani (Indonesian Journal of Educational Research and Review)
This study was intended to determine the relationship between the readiness of learning with the core competence of Indonesian language knowledge of the V grade students of SD Gugus Letkol Wisnu North Denpasar in Academic Year 2017/2018. The type of this research was ex post facto research with asymmetric correlation. The population of this study was all students of V grade students which located at SD Gugus Letkol Wisnu North Denpasar in Academic Year 2017/2018 which has population of 340 students. The determination of the sample used proportional random sampling technique with 5% error rate and obtained many samples from the population were 172 students. The data which obtained through the results of the questionnaires about the readiness of learning and the core competence of Indonesian language knowledge were obtained from recording documents value of the end semester of the core competence of Indonesian language knowledge of the V grade students of SD Gugus Letkol Wisnu North Denpasar in semester 1. As the test was a normality test data distribution. After all the prerequisite tests were fulfilled, statistical analysis used in this research was hypothesis test which used product moment correlation analysis. Based on the results of the analysis, then rxy count = 0.818. At the significance level of 5% with n = 172, then obtained rxy table = 0,148.It could be stated that rxy count = 0,818> rxy table = 0,148, hence it can be interpreted that H0 which reads there was no significant correlation between the readiness of learning with core competence of Indonesian language knowledge of the V grade students of SD Gugus Letkol Wisnu North Denpasar rejected this mean Ha accepted. Therefore, it can be concluded that there was a significant relationship between the readiness of learning with the core competence of Indonesian language knowledge of the V grade students of SD Gugus Letkol Wisnu North Denpasar in Academic Year 2017/2018, with a positive correlation direction, it means the higher the readiness of learning so that the higher the core competence of Indonesian language knowledge.